2005
DOI: 10.1021/cm047750i
|View full text |Cite
|
Sign up to set email alerts
|

Novel Star-Shaped Triphenylamine-Based Molecular Glasses and Their Use in OFETs

Abstract: Six novel star-shaped compounds with a triphenylamine core and carbazole or fluorene sidearms have been synthesized by Suzuki cross-coupling. The star-shaped molecules are able to form molecular glasses. They were characterized regarding their thermal, optical, and electrochemical properties. The new compounds were tested as organic semiconductors in solution processed organic field-effect transistors (OFETs). Mobilities of 3 × 10 -4 cm 2 /(V s), high on/off ratios of up to 10 5 , and low threshold voltages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(116 citation statements)
references
References 18 publications
(20 reference statements)
5
109
1
1
Order By: Relevance
“…26 For these studies, the various sensitizers were adsorbed on 4 mm thick transparent TiO 2 lms and excited at a wavelength of 530 nm using laser pulses with a duration of 7 ns. In order to scrutinize both processes, i.e.…”
Section: Laser Studiesmentioning
confidence: 99%
“…26 For these studies, the various sensitizers were adsorbed on 4 mm thick transparent TiO 2 lms and excited at a wavelength of 530 nm using laser pulses with a duration of 7 ns. In order to scrutinize both processes, i.e.…”
Section: Laser Studiesmentioning
confidence: 99%
“…Thin-film OFETs of compound 1 suggested that the mobility of the macrocyclic structure was much higher than that of the linear compound triphenyldiamine. [9][10][11][12][13] In this paper, we will focus on i) the crystallinity of the macrocyclic structure, ii) the synthesis of its micrometer/nanometer-sized single crystals, iii) the transport properties of the micro/nanometer-sized single crystals in OFETs, and iv) the mobility dependence of the micro/ nanocrystals on their size. It is expected that the understanding of the structure and property relationship of the macrocyclic structure will be beneficial for the further design and synthesis of materials with high crystallinity and mobility, to further extend their application in OFETs.…”
mentioning
confidence: 99%
“…Theoretical study of LB layer architecture Theoretical study of LB layer architecture Theoretical study 9 of LB layers built of fluorene derivatives can be analyzed on two planes, hydrophilic-aromatic and hydrophobic-aliphatic part of molecule. Free rotation of aromatic rings causes bigger molecular area for aromatic molecular part (~108 Å 2 ), what is also confirmed by experimental π-A isotherms.…”
Section: Properties Of Langmuir -Blodgett Films Built Of Charge Transmentioning
confidence: 99%